2004
DOI: 10.1002/bip.20189
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical properties of quadruple helices of modified human telomeric DNA

Abstract: Telomeric DNA of a variety of vertebrates including humans contains the tandem repeat d(TTAGGG)n. The guanine rich strand can fold into four-stranded G-quadruplex structures, which have recently become attractive for biomedical research. Indeed, the aptamers based on the quadruplex motif may prove useful as tools aimed at binding and inhibiting particular proteins, catalyzing various biochemical reactions, or even serving as pharmaceutically active agents. The incorporation of modified bases into oligonucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…This arises when the systems are not at thermodynamic equilibrium during the temperature changes (the scan rate used was 1.08C/min) and it is due to slow rates of dissociation or association process, indicating that these curves do not correspond to the true equilibrium curves. 17,21,33 To obtain reliable thermodynamic data, the equilibrium melting curves were derived following the procedure described in ''Materials and Methods'' section. The melting curves were obtained reporting CD signal at 263 nm as function of temperature ( Figure 3).…”
Section: Thermodynamics Of Quadruplexes Dissociationmentioning
confidence: 99%
See 2 more Smart Citations
“…This arises when the systems are not at thermodynamic equilibrium during the temperature changes (the scan rate used was 1.08C/min) and it is due to slow rates of dissociation or association process, indicating that these curves do not correspond to the true equilibrium curves. 17,21,33 To obtain reliable thermodynamic data, the equilibrium melting curves were derived following the procedure described in ''Materials and Methods'' section. The melting curves were obtained reporting CD signal at 263 nm as function of temperature ( Figure 3).…”
Section: Thermodynamics Of Quadruplexes Dissociationmentioning
confidence: 99%
“…15 Different modifications have been proposed involving the base, the phosphate group or the sugar-phosphate backbone in an attempt to stabilize quadruplex structure. [16][17][18][19][20][21] For example, it was demonstrated that a nucleic acids analogs such as peptidic nucleic acids (PNAs) can form PNA/DNA hybrid quadruplexes. 19 Unfortunately, the poor water solubility of the all PNA oligomers limits their potential applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3): (i) the heating curve shows a biphasic profile; (ii) in the cooling the CD signal is recovered in the range of temperature 105-75 • C; (iii) an hysteresis is present between melting and annealing process in the range of temperature 75-20 • C. These findings reveal the presence of a partially kinetically controlled complex melting process. Hence, to avoid kinetic control in the denaturation/renaturation processes and assure the equilibrium achievement, the CD melting curve was obtained in equilibrium conditions following a procedure previously described [39,40]. The sample was incubated at each temperature for a suitable time to achieve the equilibrium before recording the CD spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The equilibrium-melting curve was recorded in the range 15-105 • C using a temperature step of 5 • C following a previously reported procedure [39,40]. The sample was incubated at each temperature for a suitable time to achieve the equilibrium before recording the CD signal.…”
Section: Methodsmentioning
confidence: 99%